2021
DOI: 10.1021/acs.jproteome.1c00547
|View full text |Cite
|
Sign up to set email alerts
|

Novel Regulators of Retina Neovascularization: A Proteomics Approach

Abstract: The purpose of this study was to identify proteins that regulate vascular remodeling in an ROP mouse model. Pups were subjected to fluctuating oxygen levels and retinas sampled during vessel regression (PN12) or neovascularization (PN17) for comparative SWATH-MS proteomics using liquid chromatography-tandem mass spectrometry (LC-MS/MS). We developed a human retinal endothelial cell (HREC) ROP correlate to validate the expression of retina neovascular-specific markers. A total of 5191 proteins were identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“… 40 ECH1, an enzyme involved in fatty acid oxidation, was identified as an activator of NV using a proteomics approach in the murine OIR model and validated as highly up-regulated in hypoxic human retinal endothelial cells. 41 However, our findings that EMP2 blockade increases Acat1 and Ech1 expression, not decreases them, may contribute to the incomplete attenuation of neovascularization observed in our study. Last, peroxisome proliferator-activated receptor gamma (Pparγ) is upregulated by EMP2 blockade.…”
Section: Discussioncontrasting
confidence: 61%
“… 40 ECH1, an enzyme involved in fatty acid oxidation, was identified as an activator of NV using a proteomics approach in the murine OIR model and validated as highly up-regulated in hypoxic human retinal endothelial cells. 41 However, our findings that EMP2 blockade increases Acat1 and Ech1 expression, not decreases them, may contribute to the incomplete attenuation of neovascularization observed in our study. Last, peroxisome proliferator-activated receptor gamma (Pparγ) is upregulated by EMP2 blockade.…”
Section: Discussioncontrasting
confidence: 61%
“…Investigator identified a set of proteins that may be integral to the OIR retina vascular remodeling process by using liquid chromatography‐tandem mass spectrometry (LC‐MS/MS). [ 42 ] The specific mechanisms on how SHED‐apoVs affect downstream vascular remodeling protein expression through PD1/PDL1 in different stages to improve retinal structure and function remains to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…reported that CD109 was among the most down-regulated proteins in hypoxic retinal endothelial cells. Overexpression of CD109 decreased, while downregulation increased endothelial cell proliferation in both human retinal and umbilical vein endothelial cells [ 75 ]. CD109 is a GPI-anchored protein that acts as a TGF-β co-receptor and a negative regulator of TGF-β signaling.…”
Section: Discussionmentioning
confidence: 99%